Maqasid, social responsibility and Islamic investment - Barom, Mohd. Nizam (2013)
In view of recent debates and trends in Islamic finance, this paper seeks to reflect the practice of Islamic investment in the light of the Maqasid as-Shari’ah (objectives of the Shari’ah). Specifically, it attempts to argue for the incorporation of broader social responsibility concerns in the screening criteria of Islamic investment practices, and examines the attitude of investors of Islamic funds on the importance of social responsibility issues in their investment decision. The normative foundations underpinning social responsibility are discussed in the context of the contemporary understanding of the Maqasid. While the avoidance of Shari’ah prohibitions is a necessary element in developing Shari’ah-compliant finance, the promotion of the Maqasid is not complete without the presence of a positive social responsibility outlook. This is essential in sustaining and promoting the overall wellbeing of the society and the environment. In the field of Islamic investment, this necessitates the inclusion of the ‘policy-based’ methodology in the screening process of investable companies, in addition to the sector-based screening as currently practised. On the other hand, the empirical analysis suggests that the investors of Islamic funds have favourable attitude towards the importance of social responsibility issues in their investment. Further analysis using exploratory factor analysis revealed that the way the investors perceived the importance of these issues are shaped by the nature of the criteria, particularly the distinction between harm prevention and the promotion of good, and the differentiation between internal business practice and external stakeholders. Consistent with the different levels of Maslahah in the framework of Maqasid, issues clustered in ‘basic social responsibility practice’ factor are perceived to be more important than the ‘supplementary and external social responsibility’ factor by the respondents